The Influence of Leadership Style, Human Resource Quality and Organizational Citizenship Behavior (OCB) on Organizational Commitment in Communication Mediation at Bank Indonesia Representative Office in North Sumatra Province - Hendru Marpaung; Isa Indrawan (International Journal of Management, Economic and Accounting, 2024)
The first step in human resource management is to assign human resources so that they obtain work assignments that are in accordance with the work performed. Human resources (HCs) or staff members have become a top priority in any organization because their quality is crucial in facing the current business climate. This study aims to see the influence of leadership style, quality of human resources and organizational citizenship behavior (OCB) on organizational commitment in communication mediation at the Bank Indonesia Representative Office in North Sumatra Province. The results of this study are as follows: Leadership Style has a positive and significant effect on Organizational Commitment with the original sample value of 0.374 and p values of 0.001. Leadership Style had a positive and significant effect on Communication with the original sample value of 0.368 and p values of 0.001. Communication had a positive and insignificant effect on Organizational Commitment with the original sample value of 0.100 and p values of 0.179. The quality of human resources has a positive and significant effect on Organizational Commitment with the original sample value of 0.289 and p values of 0.005. The quality of human resources had a non-significant positive effect on communication with the original sample value of 0.205 and p values of 0.070. Organizational Citienship Behavior had a positive and insignificant effect on Organizational Commitment with an original sample value of 0.178 and p values of 0.053. Organizational Citizenship Behavior had a positive and significant effect on Communication with an original sample value of 0.332 and p values of 0.004. Leadership Style had an insignificant positive effect on Organizational Commitment through communication with the original sample of 0.037 and p values of 0.171. The quality of human resources has a positive and insignificant effect on Organizational Commitment through Communication with the original sample value of 0.020 and p values of 0.290. Organizational Citizenship Behavior had a positive and significant effect on Organizational Commitment through Communication with the original sample value of 0.020 and p values of 0.212.